Exploring textual meaning in Chukwuemeka Ike’s Sunset at Dawn: a systemic functional approach - KOUTCHADE, INNOCENT SOUROU; DATONDJI, COCOU ANDRÉ; SALAMI, Amadou (My University, 2018)
The goal of this research work is to apply one of the three meanings developed by Halliday (1985), the grammar of textual meaning, to two extracts selected from Chukwuemeka’s Sunset at Dawn (1976). This focus on textual meaning aims at unveiling the hidden linguistic resources or codes incorporated in the novel. It also aims at bringing out how the author of this novel has organized and established Themes to construct clauses in order to convey his message. Through a descriptive approach, the grammar of Textual meaning is studied in Chukwuemeka’s Sunset at Dawn (1976). The qualitative descriptive method used in this article is supported by a quantitative method in using descriptive statistical analysis to calculate the percentage of the different fields. The study reveals that the Theme/Rheme structure is an essential component in the construction of a cohesive and coherent text. This has enabled us to assert that Sunset at Dawn by Chukwuemeka Ike is a well-written novel
Keywords: linguistic resources; rheme; sunset at dawn; textual meaning; theme